Technical note on physical-chemical composition of Sacha inchi (Plukenetia volubilis) cake - Alcívar, J. L.; Martínez, Madeleidy; Lezcano, P.; Scull, Idania; Valverde, A. (Cuban Journal of Agricultural Science, 2020)
To chemically and physically characterize the Sacha inchi (Plukenetia volubilis) cake, samples were randomly collected, from the collection center of San Vicente canton, Manabí, Ecuador. The bromatological characterization was performed and the content of the fibrous fractions was determined. The physical properties packing volume, solubility and water adsorption capacity were analyzed. The content of anti-nutritional factors was qualitatively determined. The results showed high dry matter (89.24 %) and crude protein content (41.49 %). The fibrous fraction values were low and the physical properties showed low solubility (7.96 %), high volume (3.92 mL/g) and low water adsorption capacity (2.16 g/g). The results allow concluding that the Plukenetia volubilis (Sacha inchi) cake has adequate protein and fiber content, as well as physical properties and the presence of acceptable ANFs, which allows it to be included in animal feeding. Key words: protein cake, bromatological characterization, physical properties, anti-nutritional factors